2022
DOI: 10.21203/rs.3.rs-2380905/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and Practices of the Fourth Year Degree Nursing Students Regarding Tuberculosis Management at a University in Khomas Region, Namibia

Abstract: Background: Namibia has one of the highest incidence rates in the world reporting nearly 10 000 cases in 2015, with multi-drug resistants’ TB prevalence of between 3.9 percent for new cases 8.7 percent for previously treated cases. Regardless of Namibia being among the countries that are worst affected by TB, significant improvements have been made in the country in terms of TB diagnosis, treatment and care. Intensified screening, introduction of WHO-recommended rapid molecular testing for TB, Directly Observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Ntinda [28] states that, "in some parts of Africa, people with albinism are perceived as 'sacrificial lambs', from the biblical metaphor for someone or something that is sacrificed for the good of others. These individuals are wanted for their hands or genitals which are considered to be the body's strongest parts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ntinda [28] states that, "in some parts of Africa, people with albinism are perceived as 'sacrificial lambs', from the biblical metaphor for someone or something that is sacrificed for the good of others. These individuals are wanted for their hands or genitals which are considered to be the body's strongest parts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Article 19 of the Namibian Constitution posits that 'Every person shall be entitled to enjoy, practice, profess, maintain and promote any culture, language, tradition or religion subject to the terms of this Constitution and further subject to the condition that the rights protected by this Article do not impinge upon the rights of others or the national interest' (Republic of Namibia, 1990). The traditional cultural practices reflect the values and beliefs held by members of communities for periods often spanning generations (Ntinda, 2011).…”
Section: Cultural Levelmentioning
confidence: 99%
“…People with albinism often experience oppression and dehumanisation as in some African countries their body parts are used as aphrodisiacs, sources of wealth and prosperity, as well as a remedy to prevent cheating in sexual relationships (Ntinda, 2015). A United Nations Human Rights Council (UNHRC) report, for example, revealed that for a period of five years there were a total of 340 attacks on people with albinism and 134 murders within 25 countries (2015:5).…”
Section: Introductionmentioning
confidence: 99%